Clinical implications of blood-material interaction and drug eluting stent polymers in review. (2nd September 2017) - Mori, Hiroyoshi; Gupta, Anuj; Torii, Sho; Harari, Emanuel; Jinnouchi, Hiroyuki; Virmani, Renu; Finn, Aloke V.
ABSTRACT: Introduction : Despite advances in drug-eluting stent (DES) technology, stent thrombosis (ST) remains the most feared complication with high morbidity and mortality. Areas covered : Stent related factors certainly play a role in the pathophysiology of ST and more recent data suggest coating technologies have the potential to favorable modify this risk though blood material interactions. Of the polymer coatings used in DES, fluorinated polymers in particular have shown significant promise in modifying the risk of ST through their preferential interactions with albumin which is believed to prevent the adhesion and aggregation of platelets to the stent surface and thus minimize thrombus formation. Preclinical data from the porcine arteriovenous fistula model and clinical data from large network meta-analysis support a role for fluorinated polymers in reducing ST. Expert commentary : The search for more biocompatible anti-thrombotic polymer coatings continues and it is likely that further modification of stent based surfaces will revolutionize the field of interventional cardiology by one day obviating the need for systemic anti-platelet therapies in patients receiving intravascular devices.